Shading, lighting, and rendering with Blender's EEVEE : learn how to create and iterate amazing concept art using a real-time rendering engine - Crowder, Sammie (Packt Publishing, Limited, 2022)
Get to grips with new real-time animation techniques and tricks to improve both your artistic and technical skills in shading, 3D rendering, lighting, and scene creation using Blender 3.0 Key Features Learn real-time rendering engine concepts by creating three projects Understand how to update workflows to Blender 3.0 Explore intermediate to advanced-level tutorials on creating art inside Blender Book Description Blender is one of the most important emerging 3D software packages in the world. Anyone can download the software, and with millions of tutorials on YouTube and elsewhere, learn how to use it. EEVEE, a state-of-the-art, real-time rendering engine, is a fairly new addition to Blender and provides you with the capacity to quickly iterate on the artwork, allowing you to rapidly create, modify, and produce quality renders. This book provides a high-level overview of what EEVEE is capable of and then takes you through the steps of creating three professional-quality artworks in three unique styles. As you progress, you'll discover new techniques added in Blender 3.0, ways to add life to your renders, and mind-blowing shortcuts that will allow you to take your artwork to the next level. By the end of this Blender book, you'll have created three separate works that will have challenged you to design and iterate with the full power of Blender EEVEE. What you will learn Explore EEVEE Render Properties for optimal outcomes Focus on shading processes, including those that are both traditional and more cutting-edge Understand composition and create effective concept art inside Blender Discover procedural workflows to shorten the artistic process instead of getting mired in details Understand intermediate Blender workflows for working in a professional environment Develop art in different styles and learn why each style has different workflows and conventions Create interactive, rapid changes in Blender's EEVEE engine Who this book is for This book is for 3D animators, sculptors, modelers, and concept artists who want to use EEVEE to speed up their work in movies, TV, and game design. Readers are expected to have a basic to intermediate-level understanding of 3D programs and ray-tracing engines.